Metode Pengendalian Anak Usia Dini agar Tidak Kecanduan Gadget - Ashabul Maimanah; Alia Rohali; Khoilula Hanum Tanjung; Maysarah Rabiul Aulia Damanik; Mastianur Daulay; Rahma Yani; Annisa Hadisti Rahayu; Hilda Zahra Lubis (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Gadgets are one of the technologies that are widely used by humans. Many benefits are felt through gadgets, but if excessive use without restrictions and controls can have a bad effect on users. Moreover, if the user is an early child where this period is an important process for his life. The purpose of this study was to analyze the use of gadgets by early childhood and the role of parents in overcoming gadget addiction in children. This study uses a qualitative approach research method. The results of this study note that children use gadgets to play games, watch entertainment on YouTube which can make children learn to know shapes, reading and writing. But children often focus too much on playing gadgets, don't answer when parents call, sometimes whine when they are not given permission to play gadgets, children also seem to have problems with their speaking ability, even though children are 6 years old but there are still many words spoken by children still not understandable. In an effort made by parents to prevent negative things from using gadgets by accompanying children when using gadgets, making sure they don't view content that is not appropriate for the child's age. Keywords: Gadgets, Early Childhood